Effects of combined aerobic dance exercise and honey supplementation on bone metabolism, muscular strength and immune functions in women - Rahim, Marhasiyah (2011)
INTRODUCTION: Although combination of physical activity with supplementation has being investigated on its effects in maintaining and enhancing bone health, little is known about the effectiveness of combination of aerobic dance exercise with honey supplementation on bone metabolism markers, muscular strength and immune function in women. PURPOSE: The aim of this study was to investigate the effects of combined aerobic dance exercise and honey supplementation on bone metabolism, muscular strength and immune function in women. METHODS: Forty four subjects, healthy sedentary women (25-40 year-old) were age and body mass matched, and subsequently being assigned into four groups with n=11 per group: Control group (C), honey supplementation group (H), aerobic dance exercise group (Ex) and combined aerobic dance exercise with honey supplementation group (HEx). Aerobic dance exercise was carried out for one hour per session, three times per week for eight weeks. Honey drink was consumed by H and HEx groups, in a dosage of 20g of honey diluted in 300ml of plain water, for 7 days per week for a total of 8 weeks duration. In HEx group, the subjects were required to consume honey drink 30 minutes before performing exercise on the exercise days. Before and after 8 weeks of experimental period, subjects’ anthropometry, muscular strength and power were measured. Meanwhile, blood samples were taken in order to determine the concentrations of serum total calcium, osteocalcin (bone formation marker), serum C-terminal telopeptide of type 1 collagen (1CTP) (bone resorption marker), and parathyroid hormone (PTH), and immune functions determination through full blood counts and immunophenotyping measurements. RESULTS: The end of 8 weeks of experimental period, combination of aerobic dance exercise with honey supplementation (HEx) exhibited more discernable beneficial effects on left and right lower limb peak torque (muscular strength) and power compared to the other three Ex, H and C groups. Regarding bone metabolism, the percentage of increment in 1CTP, a bone resorption marker, and PTH concentrations in HEx group were the lowest compared to the other experimental groups. With regards to immune functions, significant increases in T cytotoxic (CD8) and total B cells (CD19) counts (p<0.05) were observed in HEx group after 8 weeks of experimental period. Additionally, the percentage increase in lymphocyte counts, T helper (CD4), T cytotoxic (CD8) and total B cells (CD19) counts after 8 weeks were the highest in HEx group compared to the other three experimental groups. CONCLUSION: The results of present study suggest that combination of aerobic dance exercise and honey supplementation elicited more beneficial effects on bone health, muscular strength and power, and immune functions generally compared to aerobic dance exercise or honey supplementation alone in sedentary women.